Peran Pendidikan Pancasila dalam Membentuk Karakter Anti Perundungan di Lingkungan Sekolah Dasar - Faza Brilliani Wahono Putri; Fathurrohman (CV. Kurnia Grup, 2026)
The phenomenon of bullying in the elementary school environment is still a serious problem that has a negative impact on the social and emotional development of students. Character education that has been implemented in various schools is often not fully effective because it has not been systematically integrated with the nation's ideological values. Therefore, this study aims to analyze the role of Pancasila Education in forming anti-bullying characters in elementary school students. This study uses a descriptive qualitative approach with a literature study method (library research). Data was obtained from a variety of scientific sources, such as national journals, books, and relevant research reports published in the last five years. The results of the study show that Pancasila Education has a strategic role in instilling the values of humanity, social justice, and unity which are the basis for the formation of students' character. These values are able to foster empathy, respect, and social responsibility so that students have the awareness to reject all forms of bullying. In addition, the success of the implementation of Pancasila Education is greatly influenced by the role of teachers as moral role models and collaboration between schools, families, and communities. The conclusion of this study emphasizes that strengthening Pancasila Education needs to be carried out contextually and collaboratively in order to create a school culture that is peaceful, inclusive, and has Pancasila character.